Selective palladium-catalyzed dehydrogenation of limonene to dimethylstyrene - Horrillo Martínez, Patricia; Virolleaud, Marie‐Alice; Jäkel, Christoph (ChemCatChem, 2010)
Conditions for the selective dehydrogenation of (+)-limonene 1 to the polymer building block dimethylstyrene 2 are described. The reaction occurs smoothly in the presence of Pd(OTFA)2 as catalyst and CuCl2 as oxidant. High selectivity for retaining the exocyclic double bond during aromatization is achieved (>14:1). Initially, variable-temperature NMR experiments, under stoichiometric conditions, showed a stepwise formation of a π-allyl intermediate and subsequent reaction to give a mixture of products. However, kinetic experiments showed a sigmoidal curve, pointing to the heterogeneous nature of the catalytically active species. A number of experiments were undertaken to differentiate between homogeneous, molecularly defined catalysis and heterogeneous, nanocluster-based catalysis. Based on the results, it is proposed that the true catalytic system is heterogeneous in nature.
First published: 01 February 2010
Gesehen am 17.04.2023